The Rainforests of Cameroon : Experience and Evidence from a Decade of Reform - Topa, Giuseppe (World Bank, 2012)
In 1994, the Government of Cameroon introduced an array of forest policy reforms, both regulatory and market-based, to support a more organized, transparent, and sustainable system for accessing and using forest resources. This report describes how these reforms played out in the rainforests of Cameroon. The intention is to provide a brief account of a complex process and identify what worked, what did not, and what can be improved. The barriers to placing Cameroon's forests at the service of its people, its economy, and the environment originated with the extractive policies of successive colonial administrations. The barriers were further consolidated after independence through a system of political patronage and influence in which forest resources became a coveted currency for political support. These deeply entangled commercial and political interests have only recently, and reluctantly, started to diverge. In 1994, the government introduced an array of forest policy reforms, both regulatory and market based. The reforms changed the rules determining who could gain access to forest resources, how access could be obtained, how those resources could be used, and who will benefit from their use. This report assesses the outcomes of reforms in forest-rich areas of Cameroon, where the influence of industrial and political elites has dominated since colonial times.